2020
DOI: 10.1002/jcaf.22459
|View full text |Cite
|
Sign up to set email alerts
|

Accounting comparability and the value relevance of earnings and book value

Abstract: The value relevance of financial statements is of great significance to investors and standard setters. The present research examines whether accounting comparability among industry peers enhances the value relevance of earnings and book value. This is an important question because both the Financial Accounting Standards Board and the Securities Exchange Commission seek greater comparability in financial reporting. However, there is limited empirical evidence on how comparability affects the value relevance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
0
9
0
6
Order By: Relevance
“…For instance, De Franco et al (2011 and Barth et al (2012) show that earnings quality matters to accounting comparability. Chen et al (2020) show that financial reporting opacity and internal control material weakness attenuate, while industry specialized auditors enhance, the positive relationship between accounting comparability and the value relevance of earnings. Dechow (1994) finds that the importance of accruals is greater for firms with shorter performance measurement intervals, more volatile working capital requirements and investment and financing activities and longer operating cycles.…”
Section: Effects Of Earnings Quality and Product Similaritymentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, De Franco et al (2011 and Barth et al (2012) show that earnings quality matters to accounting comparability. Chen et al (2020) show that financial reporting opacity and internal control material weakness attenuate, while industry specialized auditors enhance, the positive relationship between accounting comparability and the value relevance of earnings. Dechow (1994) finds that the importance of accruals is greater for firms with shorter performance measurement intervals, more volatile working capital requirements and investment and financing activities and longer operating cycles.…”
Section: Effects Of Earnings Quality and Product Similaritymentioning
confidence: 92%
“…De Franco et al (2011 confirm this assertion by finding that accounting comparability helps improve the information environment and lowers the cost of information acquisition. Furthermore, recent studies find that accounting comparability improves a wide variety of firm outcomes (Kim et al, 2013;Kim et al, 2016;Young and Zeng, 2015;Imhof et al, 2017;Neel, 2017;Zhang, 2018;Chen et al, 2020).…”
Section: Accounting Comparabilitymentioning
confidence: 99%
“…The results of their research showed that the combined relationship between book value and profit with company value did not change significantly during the study period. However, the relationship between book value and company value has increased regularly while the relationship between profit and company value has been continuous in this review (Chen et al, 2020). The main objective of this research is to know whether the accounting comparability of profit value relevance increases profit book value or not?…”
Section: Problem Statementmentioning
confidence: 98%
“…Therefore, increasing comparability increases the likelihood of detecting manipulation and fraud in financial statements and reduces the motivation of managers to commit fraud. In other words, it is expected from firms with low comparability in their financial statements to fraud more than other firms (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu relevansi nilai laporan keuangan sangat penting bagi investor. (Chen, Kurt, & Wang, 2020) Penelitian dengan menggunakan laporan keuangan dalam mengetahui dampaknya terhadap harga saham telah banyak dilakukan.…”
Section: Penelitian Terdahuluunclassified